Tumor suppression effect of targeting periostin with siRNA in a nude mouse model of human laryngeal squamous cell carcinoma. Issue 1 (5th July 2018) - Ye, Dong; Zhou, Chongchang; Wang, Sijia; Deng, Hongxia; Shen, Zhisen
Abstract : Background: The incidence of laryngeal carcinoma is increasing, however, the mechanism is not fully understood. We aimed to investigate the efficacy of periostin gene silencing by siRNA on tumor inhibition, in a novel nude mouse model of human laryngeal squamous cell carcinoma, and to explore possible inhibitory mechanisms. Methods: Tumors were established in nude mice by transplantation of LSCC AMC‐HN‐8 cell line. Forty‐eight nude mice were randomly divided into groups of eight each, and treated with high (1.0 OD) or low (0.5 OD) doses of periostin‐siRNA or appropriate control solutions. Tumor growth was observed and used to calculate an inhibition rate (%). Routine pathological and electron microscopic examination were used to determine tumor apoptosis and proliferation. Changes in periostin mRNA and protein levels were analyzed. Results: Tumor growth was significantly inhibited in mice treated by high dose periostin‐siRNA compared to untreated and those treated with low dose periostin‐siRNA ( P  <   0.05). Pathological examination showed increased tumor necrosis and apoptotic changes in treated mice, which was confirmed by electron microscopy. Periostin mRNA and protein expression were significantly reduced in tumors from mice treated with high dose periostin‐siRNA, compared to controls and low‐dose periostin‐siRNA treatment groups ( P  < 0.05). Conclusion: Periostin silencing was associated with growth inhibition of tumor cells in a nude mouse model of LSCC. The underlying mechanism may be due to receptor‐mediated induction of relevant signal transduction pathways that modulate the microenvironment needed for cancer cell survival. Periostin is expected to become a new target for cancer therapy.